Calibration of a digital camera for close-range photogrammetry application - Alias, Nor Azira; Setan, Halim; Majid, Zulkepli (2008)
Lately, close-range photogrammetry became more popular to model any objects in varies field. With the advent of powerful computers and cheap optical devices, photogrammetric methods are now being implemented in several aspects of medicine. The body shape measurement such as craniofacial mapping is included of close-range photogrammetry applications. Compared with other technique like laser scanning, digital close-range photogrammetry is more cost-effective, flexible and easy to use. Integrated with new commercial three-dimensional (3D) modeling and measurement software such as PhotoModeler Scanner that can be used with many digital cameras, it was very effective technique. However, to give high-accuracy results, the cameras must be calibrated to determine parameter of the camera that will be used. The paper presents the camera calibration (Sony DSC-F828 digital camera) using the new 3D software, PhotoModeler Scanner and the results will be compared with the Australis 6.0 software.